2013
DOI: 10.1002/jbm.a.34702
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of simvastatin from premixed injectable calcium phosphate cement

Abstract: Locally applied simvastatin is known to promote bone regeneration; however, the lack of suitable delivery systems has restricted its clinical use. In this study we demonstrate for the first time the use of premixed acidic calcium phosphate cement (CPC) as a delivery system for water-solubilized simvastatin. Freeze-dried simvastatin β-hydroxy acid (SVA) was added to the premixed cement paste in four different doses (1, 0.5, 0.25, and 0 mg SVA/g cement). The addition of the drug did not alter the cement setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
(73 reference statements)
3
16
0
Order By: Relevance
“…In the current work, the unaltered handling properties of the paste: cohesion (Figure 2), setting times (Table 1) and injectability ( Figure 3) suggested that the addition of simvastatin did not modify the workability of the paste, as suggested elsewhere [23]. Although simvastatin did not prevent the transformation of the reagents into rhombohedric crystals of brushite ( Interestingly, s-C-3m showed the highest porosity and the lowest tortuosity factor of all (Figure 7b).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In the current work, the unaltered handling properties of the paste: cohesion (Figure 2), setting times (Table 1) and injectability ( Figure 3) suggested that the addition of simvastatin did not modify the workability of the paste, as suggested elsewhere [23]. Although simvastatin did not prevent the transformation of the reagents into rhombohedric crystals of brushite ( Interestingly, s-C-3m showed the highest porosity and the lowest tortuosity factor of all (Figure 7b).…”
Section: Discussionsupporting
confidence: 74%
“…In a previous study using premixed brushite cement as carrier of simvastatin (a similar amount, of 0.25 mg simvastatin/g cement) [23] a slow drug release was observed and almost all drug was released after 7 days. The drug release pattern for the premixed brushite cement was similar to the one observed for the aqueous brushite cement s-C-15h, which could indicate a high tortuosity factor of the premixed cement.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, to overcome this problem, polymers such as poly(β-amino ester) (PBAE) [18], polyethylene glycol (PEG) [19], and poly(L-lactic acid) (PLLA) [20] were added to adjust the release profile of the drug. Inorganic porous materials were also used as bone substitutes, such as α-tricalcium phosphate (α-TCP) [21], β-tricalcium phosphate (β-TCP) [2224], and hydroxyapatite (HA) [18]. SIM was also mixed with these materials to be drug delivery scaffolds.…”
Section: Introductionmentioning
confidence: 99%